2013
DOI: 10.1088/0004-637x/777/1/36
|View full text |Cite
|
Sign up to set email alerts
|

The Exemplar T8 Subdwarf Companion of Wolf 1130

Abstract: We have discovered a wide separation (188. 5) T8 subdwarf companion to the sdM1.5+WD binary Wolf 1130. Companionship of WISE J200520.38+542433.9 is verified through common proper motion over a ∼3 yr baseline. Wolf 1130 is located 15.83 ± 0.96 pc from the Sun, placing the brown dwarf at a projected separation of ∼3000 AU. Near-infrared colors and medium resolution (R ≈ 2000-4000) spectroscopy establish the uniqueness of this system as a high-gravity, low-metallicity benchmark. Although there are a number of low… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 107 publications
3
91
0
Order By: Relevance
“…T dwarfs in higher order multiple systems are relatively rare, this being the fifth such system discovered after Gl 570 D (Burgasser et al 2000),Wolf 1130 B (Mace et al 2013), Ross 458 C (Goldman et al 2010) and ξ UMa E (Wright et al 2013). The central binary of 2MASS J0213+3648 has Hα and X-ray activity along with UV flaring, suggesting that it may be young (with the X-ray emission pointing towards it being younger than the Hyades).…”
Section: O N C L U S I O N Smentioning
confidence: 99%
See 1 more Smart Citation
“…T dwarfs in higher order multiple systems are relatively rare, this being the fifth such system discovered after Gl 570 D (Burgasser et al 2000),Wolf 1130 B (Mace et al 2013), Ross 458 C (Goldman et al 2010) and ξ UMa E (Wright et al 2013). The central binary of 2MASS J0213+3648 has Hα and X-ray activity along with UV flaring, suggesting that it may be young (with the X-ray emission pointing towards it being younger than the Hyades).…”
Section: O N C L U S I O N Smentioning
confidence: 99%
“…Currently, there are 22 known T dwarf companions with separations greater than 100 au, the 21 listed in the literature review of Deacon et al (2014) plus the recently discovered companion to the exoplanet host star HIP 70849 (Lodieu et al 2014). Of these, four (Gl 570 D, Burgasser et al 2000; Wolf 1130 B, Mace et al 2013; Ross 458 C, Goldman et al 2010, and ξ UMa E, Wright et al 2013) lie in systems with higher order stellar multiplicity. Relatively few known T dwarfs companions lie in young systems.…”
mentioning
confidence: 99%
“…This is not surprising when one considers Figure 3. These plots place WISE J0304-2705 in the colour-spectral-type space of the late-T and Y dwarf population (data from Leggett et al 2013;Mace et al 2013b;Pinfield et al 2014;Kirkpatrick et al 2014;Burningham et al 2014), and it can be seen that WISE J0304-2705 occupies essentially the same colour space as the previously known Y0 dwarfs, though at the bluer end in J − W 2 and H − W 2. Our best estimate for the distance of WISE J0304-2705 is thus 10-17 pc, appropriate for a single object.…”
Section: Distance Kinematics and Reduced Proper Motionmentioning
confidence: 58%
“…Reduced proper motion (HW 2 = W 2 + 5 log µ + 5) is shown against both W 1−W 2 colour and spectral type, with disk L and T dwarfs shown as filled blue circles, and other Y dwarfs in green. Sub dwarfs from the thick-disk/halo are blue open circles (L dwarfs) or orange symbols (T dwarfs; Mace et al 2013b;Pinfield et al 2014;Burningham et al 2014). Black lines delineate Vtan ranges within the diagrams, and WISE J0304-2705 can be seen to lie in the middle of the Y dwarf population.…”
Section: Distance Kinematics and Reduced Proper Motionmentioning
confidence: 99%
“…From studies of stars, tangential velocities of objects in the thick-disk have been found to be ∼85-180 km s −1 (e.g., Fuhrmann 1998;Feltzing et al 2003;Soubiran et al 2003) and ∼200-300 km s −1 in the halo (e.g., Chiba & Beers 2000;Schilbach et al 2009;Mace et al 2013b). With a tangential velocity of ∼170km s −1 , WISE J0711-5736 lies right on the cusp between these populations.…”
Section: Halo/thick-disk Brown Dwarfsmentioning
confidence: 99%